A FURTHER CONSIDERATION OF THE PURPOSE OF THE SECOND COLUMN OF THE HEXAPLA - Emerton, John Adney (The journal of theological studies, 1971)
J. A. EMERTON; A FURTHER CONSIDERATION OF THE PURPOSE OF THE SECOND COLUMN OF THE HEXAPLA, The Journal of Theological Studies, Volume XXII, Issue I, 1 April 197